Structural Design of Partitioned Stator Doubly Salient Permanent Magnet Generator for Power Output Improvement - Warat Sriwannarat; Apirat Siritaratiwat; Pirat Khunkitti (Advances in Materials Science and Engineering)
Partitioned stator doubly salient permanent magnet generators (PS-DSPGs) have been extensively used for electrical generation mainly due to their high reliability, high electromotive force (EMF), and high-power output. Therefore, we aim to improve the output power of a PS-DSPG by designing the optimal configuration of generator pole structure. Electrical characteristics including the magnetic flux linkage distribution, phase EMF, cogging torque, voltage regulation, and power output profile were characterized by using the finite element method. After optimizing the generator pole structure including the angle of air gap arc width, it was found that the proposed PS-DSPG with 18/15 (stator/rotor) pole structure with optimized air gap arc width could produce higher EMF of about 23.24% than a conventional structure because this structure has the suitable number of pole structures. Also, an analysis of voltage regulation and power output profiles under the loaded condition were carried out, and it was indicated that the PS-DSPG based on the suitable 18/15-pole structure could provide the best machine performance where the output power is 11.63% higher than the conventional structure. Hence, the proposed PS-DSPG with 18/15-pole structure can appropriately be utilized for electrical generation, especially in low-speed operated generator applications.